1996
DOI: 10.1002/(sici)1097-0185(199601)244:1<70::aid-ar7>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morphology of the pituitary gland in Australian flying foxes (megachiroptera: GenusPteropus)

Abstract: Background Investigations of reproductive endocrinology of flying foxes (genus Pteropus) have been hampered by inadequate information on the normal morphology of the megachiropteran pituitary. Methods The novel technique of graphical three‐dimensional (3‐D) reconstruction, supported by more traditional anatomical techniques, have now been used to examine the shapes of, the interrelations between, the lobes of the pituitary of the little red flying fox, Pteropus scapulatus. Statistical analysis of data from thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The influence of pituitary hormones, such as, LH, FSH and prolactin are fundamental to reproductive physiology. These cells of pars distalis not only play a pivotal role in reproductive processes of mammals but also show changing morphology during different phases of reproductive cycle of bats (Herlant, 1962;Peyre & Herlant, 1963;Badwaik, 1988Badwaik, , 1991Richardson, 1979;O'Brien et. al., 1996;O'Brien, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of pituitary hormones, such as, LH, FSH and prolactin are fundamental to reproductive physiology. These cells of pars distalis not only play a pivotal role in reproductive processes of mammals but also show changing morphology during different phases of reproductive cycle of bats (Herlant, 1962;Peyre & Herlant, 1963;Badwaik, 1988Badwaik, , 1991Richardson, 1979;O'Brien et. al., 1996;O'Brien, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, the pituitary gland itself has rarely been studied for correlations with the biological processes it controls, or even for its variability in size. This may be due to the difficulty of studying a small organ that is best visualized by histological study (e.g., Patil, ; Anthony and Gustafson, ; King et al, ; Badwaik, ; Bhiwgade et al, ; O'Brien, ; Anthony, ; Azzali et al, ). The size of the hypophysis was studied by Legait et al (), and Bauchot and Legait (), who measured volume of the hypophysis in 50 species of bats.…”
Section: Introductionmentioning
confidence: 99%
“…The hypothalamic‐pituitary pathway achieves central control of endocrine support of reproduction in bats (Anthony, ). The hypophysis of some commonly studied bats, such as Myotis, Hipposideros , and Pteropus have been microscopically studied (Anthony and Gustafson, ; O'Brien, ), and Legait et al () provided the only study of bat hypophyseal volumes to date. Previously, emphasis has not been placed on the pituitary gland as a compound structure, which is part glandular, part neural.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of pituitary hormones, such as LH and FSH are fundamental to reproductive physiology. These cells of pars distalis not only play a pivotal role in reproductive process of mammals but also show changing morphology during different phases of reproductive cycle of bats [ 4 5 9 24 26 23 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Herlant [ 8 ], Peyre and Herlant [ 25 ], Badwaik [ 4 ] and O’Brien et. al [ 24 ] have reported that these cell have different morphological feature at different reproductive phases. In the present study ultrastructure of FSH and LH are described with reference to Golgi body, Endoplasmic reticulum, secretory vesicles, mitochondria and nucleus.…”
Section: Introductionmentioning
confidence: 99%